Frères Ennemis The French in American Literature, Americans in French Literature - Cloonan, William (Liverpool University Press, 2018)
Frères Ennemis ocuses on Franco-American tensions as portrayed in works of literature. An Introduction is followed by nine chapters, each focused on a French or American literary text which shows the evolution/devolution of the relations between the two nations at a particular point in time. While the heart of the analysis consists of close textual readings, social, cultural and political contexts are introduced to provide a better understanding of the historical reality influencing the individual novels, a reality to which these novels are also responding. Chapters One through Five, covering a period from the mid-1870s to the end of the Cold War, discuss significant aspects of the often fraught relationship from the theoretical perspective of Roland Barthes' theory of modern myth, described in his Mythologies. Barthes' theory helps situate Franco-American tensions in a paradigmatic structure, while at the same time it is supple enough to allow for shifts and reversals within the paradigm. Subsequent chapters explore new French attitudes toward the powerful, potentially dominant influence of American culture on French life. In these sections I argue that recent French fiction displays more openness to the American experience than has existed in the past, and as such contrasts with the more static American approach to French culture.